„Calendar Theatre”.Dramaturgy of performances commemorating the March 1968 - Kosieradzka, Karolina (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
Creating performances for the celebration of important events is not a modern invention, but it is an extremely interesting phenomenon due to the ability to respond to the needs of given times, the range of impact (territorial and reception), and usually a short operating time. The fiftieth anniversary of March 1968 was full of performances dealing with the emigration of Polish citizens of Jewish origin who were forced to leave by launching an anti-Semitic campaign.In my paper, I will analyze the dramaturgy of three performances: A Few Foreign Words in Polish directed by Anna Smolar with a text by Michał Buszewicz created for a specific production, Michał Zadara's Justice as a theatrical investigation into a crime involving King Oedipus by Sophocles and Notes from exile directed by Magda Umer and adapted from a book by Sabina Baral.Despite the common starting point, which is the theme of the events of March 1968, the aforementioned performances are characterized by a different approach to both the undertaken problem and dramatic solutions. The main concept of the paper is "postmemory", that is the structure of the transfer of trauma between generations, and its subsequent redefinitions. An important issue will also be examining the relationship between memory and history, the function of photography and the principles of building a postmemory archive.